2008
DOI: 10.1149/1.2969947
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Source of Evolved Gas in Li-Ion Batteries Using [sup 13]C-labeled Solvents

Abstract: In order to elucidate the mechanism of gas evolution in lithium-ion batteries, we fabricated carbon-LiNi x Co y Al 1−x−y O 2 cells employing 13 C-labeled ethylene carbonate ͑ 13 C-EC͒ and diethyl carbonate ͑ 13 C-DEC͒ as solvent components and then stored them at 85°C. The gas species evolved during storage tests were analyzed by gas chromatography/atomic emission detector to determine the isotopic ratio of CO 2 and CO. The relative proportions of the CO 2 derived from EC, DEC, and nonsolvent components were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
177
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(196 citation statements)
references
References 23 publications
18
177
1
Order By: Relevance
“…This is qualitatively consistent with the study by Onuki et al 21 who showed that roughly two thirds of the CO 2 and CO produced during 85…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is qualitatively consistent with the study by Onuki et al 21 who showed that roughly two thirds of the CO 2 and CO produced during 85…”
Section: Resultssupporting
confidence: 93%
“…. ), whereby CO 2 is found to be the main product in the absence of added water (CO 2 /CO ratio > 6:1, see Table II), consistent with the observations by Onuki et al 21 In the presence of water, the CO 2 /CO ratio increases substantially ( 10:1, see Table II), suggesting that water favors the reaction pathway of EC to CO 2 . A mechanism for this reaction is proposed in our forthcoming article.…”
Section: Contribution Of Pvdf Tosupporting
confidence: 90%
See 1 more Smart Citation
“…With surface spectroscopy and chemical synthesis he and coworkers determined the major products of organic carbonates from surface reduction to be semi-carbonates that are generated via a single-electron pathway [9]. More recent spectroscopic as well as diagnostic studies further confirmed Aurbach's findings while adding an alternative two-electron pathway leading to oxalates and alkoxides (Scheme 1) [16,17].…”
Section: Chemistry and Formation Mechanism Of Seimentioning
confidence: 95%
“…The CO 2 detected could originate from side reactions with the electrolyte, surface contaminants, or from excited O release from the oxide electrode. 42,43 Beginning at ∼4.0 V, there was a burst of O 2 evolution not explained by electrolyte oxidation, suggesting that lattice oxygen ions were directly involved in the redox reaction. 9,21 The gas evolution measurement provides useful insights into the understanding of anionic oxygen redox during charge, especially in the high voltage region.…”
Section: ■ Introductionmentioning
confidence: 99%